2020
DOI: 10.1177/1591019920950889
|View full text |Cite
|
Sign up to set email alerts
|

Radial artery neuro guide catheter entrapment during mechanical thrombectomy for acute ischemic stroke: Rescue brachial plexus block

Abstract: To our knowledge, radial artery catheter entrapment during mechanical thrombectomy for acute ischemic stroke using an 8 F neuro guiding catheter (.088 in ID) and successful use of a brachial plexus block has not been described in the literature. In this technical note, we describe a patient that underwent rapid and successful radial access mechanical thrombectomy for an acute right middle cerebral artery occlusion, however, during withdrawal of the Balt Ballast 0.088 inch long sheath (Balt USA, Irvine, CA, USA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 8 publications
0
3
0
Order By: Relevance
“…8 F neuro long guide sheaths have an outer diameter of approximately 2.8 mm, which is larger than the average radial artery diameter in a significant proportion of patients. 17 When the diameter of the radial artery was less then 2.5 mm, Benchmark guiding catheter instead of a larger bore guiding catheter was used. Stampfli et al performed LVOs MT with 5F SOFIA in 115 cases.…”
Section: Discussionmentioning
confidence: 99%
“…8 F neuro long guide sheaths have an outer diameter of approximately 2.8 mm, which is larger than the average radial artery diameter in a significant proportion of patients. 17 When the diameter of the radial artery was less then 2.5 mm, Benchmark guiding catheter instead of a larger bore guiding catheter was used. Stampfli et al performed LVOs MT with 5F SOFIA in 115 cases.…”
Section: Discussionmentioning
confidence: 99%
“…16 Importantly, we had no cases of catheter entrapment in the radial artery, a complication that has been reported with other ACs. 17 Lin et al described using a 0.088 ′′ ID AC, via a femoral approach, for flow diversion and treatment of intracranial aneurysm; they reported an access site complication rate of 1.1% (1/95; groin hematoma) and a 1.1% (1/95) rate of carotid dissection. 9 Likewise, Bageac et al reported their experience in 42 patients with using a new 0.088 ′′ ID AC, via a femoral approach, for flow diversion; they reported a dissection rate of 2.3% (1/44 interventions).…”
Section: Advantages Of the Bmx96mentioning
confidence: 99%
“…In complex epiaortic vessel anatomy (e.g., bovine arch, type III aortic arch, extracranial tortuosity/kinking/loop), TRA catheterization is expected to be much less time-consuming than the TFA approach. As for today, the critical drawback of TRA-MT is the forced choice between either sheathless 8F guide catheters, designed for femoral approach and carrying a higher risk of spasm/catheter entrapment [ 2 ], or 6F low-profile sheath and 6F guide catheters, with a significant downsizing of the aspiration catheter diameter [ 3 ]. Shortly after the new RED aspiration catheter family from Penumbra came to market in late 2022, it was noted that the thinnest one (RED 62) was fully compatible with a 7F guide catheter (e.g., Rist; Medtronic or Fubuki; Asahi Intecc Co., Ltd.).…”
Section: Introductionmentioning
confidence: 99%